Ivermectin as a possible ally in the treatment of COVID-19: perspectives on its antiviral action (Research, Society and Development, 2020)
The outbreak of infections caused by the SARS-CoV-2 has affected the health of a large number of people worldwide, without a consolidated therapy with proven benefit for reducing morbidity and mortality in the early stages of COVID-19. In view of this, the already known viricidal action of ivermectin has fostered studies that established the effectiveness of this drug as a therapeutic option in the clinical treatment of the disease. Thus, this article seeks to summarize the main and most recent evidence of the antiviral effect of ivermectin in the treatment of SARS-CoV-2 infection. The guideline PRISMA 2009 and the PICOS strategy were used as the basis for the study. The articles were searched using the “advanced” tool in the PubMed database, where the association between the pre-established MeSH descriptors and the Boolean operators AND and OR was used, and 10 articles were found. Among these, after applying the eligibility criteria, 4 papers were included in this study. The results revealed that interventions using ivermectin in vitro for 48 hours are statistically significant, decreasing viral replication by up to 5000 times. However, the effectiveness of the drug in vivo against SARS-CoV-2 still needs investigation, and clinical studies are necessary in order to elucidate this problem.